Survey The Factors Affecting Relationship Marketing With Emphasis On The Role Of Buyer-Seller Relationship Quality - N. Badrtdinov, Nail (2019)
The purpose of this paper are a few topics. First, how can a purchasing company consider whether its key supplier network image is currently in line with the key supplier network format? Second, how can a purchasing company become aware that key supplier network images may benefit from the revision? Third, how can a buying company overtake new insights, which may lead to a revision of key supplier network images and the creation of new actions and responses to key suppliers. Result of our surveys, to create a competitive advantage, industrial marketers need to have the knowledge and skills needed to manage communication with their customers. Relational marketing should seek for a relationship that will lead to customer repurchase. This is achieved through satisfaction and customer value. In the industrial market, customer and supplier relationships are a source of competitive advantage. Relational marketing must identify and create value for its customers on a continuous basis so that the interests of both parties are taken into account. The relationships between the organization and its suppliers are vital to any organization. Providers can directly influence the financial performance and profitability of the company through purchasing activity, and their impacts will be on product development costs, inventory levels, production planning, production rates, timely product delivery and services. Supply chain management is a way to enhance the competitive advantage that is becoming increasingly important. Long-term relationships between suppliers and buyers reduce buyers' uncertainty. And this is perhaps the most important reason industrial marketers are looking for a long-term relationship. Industrial relations need to be recognized and worked on to develop and improve it so that the needs and goals of the company can best be met.